Video-assisted thoracoscopic lobectomy for congenital cystic adenomatoid malformations - Amina Selimović; Edo Hasanbegović; Ermina Mujičić; Selma Milišić; Emir Haxhija; Kenan Karavdić; Alen Pilav (Medicinski glasnik, 2017)
Aim: The aim was to show rare cases of congenital cystic adenomatoid malformation (CCAM) and the manner of its surgical treatment with video-assisted thoracoscopic surgery (VATS). Methods: Two male and one female child, 7, 4 and 3 years of age were treated for symptoms of cough and high temperature in district hospitals. In all three children laboratory blood tests and chest radiography were done. Auscultatory findings showed the presence of pneumonia. Children were treated with appropriate doses of antibiotics. After the rehabilitation of inflammation, they were sent to the University Clinical Center Sarajevo, where video-assisted thoracoscopic lobectomy (VATS) was indicated after computerized tomography (CT). Results: Chest CT scan pointed to the CCAM and pulmonary sequestration (PS) changes to the lungs. This has required surgery lobectomy of an affected part of the lungs. In two children with PS, the aberrant systemic artery came from the most proximal part of aorta abdominals, the third patient did not have an anomalous artery. Conclusion: VATS lobectomy is an alternative to the traditional thoracotomy for the treatment of CCAM and PS, however, it should be investigated in the future for its safety and effectiveness.
Keywords: lung malformation; thoracoscopic surgery; pulmonary sequestrations; cystic adenomatoid